From xray to display: A quality management system workflow for production and visualization of radiological images. (September 2016) - Di Lorenzo, R.; Paolucci, M.; Didona, A.; Lotti, E.
Abstract : Introduction: In 2013 the unification of two different public health companies led to the need of technological integration of RIS-PACS system in order to optimize the patient data management of all the diagnostic radiology department. Purpose: Implementation of a quality assurance program, following the national and international laws and regulations, of xray imaging production and visualization system, integrated in the ISO 9001:2008 standards. Materials and methods: Quality Assurance (QA) program is developed in many steps, starting from census and classification of all the equipment (Computed Radiography, Direct Radiology, Work Station, ecc.), through acceptance tests and constancy test program, made in association with the radiology department staff. The activity involved different instrumentation and home-made software, made by open source solution, dedicated to the management of data acquisition and analysis. Results: Quality management system allows us to check in real time all the display, using a dedicated software platform controlled from the Medical Physics Department office, with a time sparing related to the huge extension of the local health trust. Conclusions: The QA program of CR and DR system, after three years, led the possibility to renew the oldest equipment and, at the same time, the optimization of the image quality related to dosimetric parameters, following the ALARA principles, with a better uniformity of image reporting.